KEPUASAN NASABAH DALAM MENINGKATKAN MINAT MEREKOMENDASIKAN - Saputra, Whisnu Adi (Master of Management Diponegoro University, 2015)
The purpose of this reserh is to test the influenes of benefit advantage and servie advatage on customer satisfaction to increase word of mouth intention. Using these variables, the usage of these variables are able to solve the arising problem within PT.Bank Jateng apem Kagok SemarangThe samples size of this research is 100 customers PT Bank Jateng Capem KAgok Semarang. Using the Structural Equation Modeling (SEM). The results show that the benefit advantage and service advantage on customer satisfaction to increase word of mouth intention.The effect of benefit advantage on customer satisfaction are 0,44. The effect service advantage onÂ customer satisfaction are 0,27, and The effect customerÂ satisfaction on word of mouth intention 0.43.Â